2015
DOI: 10.1155/2015/543070
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Silicosis Presents with Pleural Effusion

Abstract: Silica and silicate mineral dust inhalation can cause a variety of histopathological changes in the lungs and pleura. These include pulmonary silicotic nodules, interstitial infiltrate, fibrosis, and pleural thickening. Pleural effusion is an extremely rare presentation of silicosis. To our best knowledge, there have been only 2 cases of silicosis with pleural effusion reported in medical literature. Herein, we describe a case of a 77-year-old male with almost 50 years' history of occupational silica exposure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…However, in that study, pleural fluid analysis, elemental analysis, and examination of birefringent particles compatible with silicosis using polarized light were not performed. Only three case studies have reported pleural fluid analysis results in patients presenting with pleural effusion possibly due to chronic silicosis [ 5 , 7 , 8 ]. The pleural effusion in all these cases was exudative, and like in our case, it was lymphocyte-predominant in two other cases [5, 7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in that study, pleural fluid analysis, elemental analysis, and examination of birefringent particles compatible with silicosis using polarized light were not performed. Only three case studies have reported pleural fluid analysis results in patients presenting with pleural effusion possibly due to chronic silicosis [ 5 , 7 , 8 ]. The pleural effusion in all these cases was exudative, and like in our case, it was lymphocyte-predominant in two other cases [5, 7].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of silica in the pleural effusion was not analyzed in all reported cases. Interestingly, over 25–50 years had passed from the start of silica exposure to the onset of the pleural effusion in all the three cases [ 5 , 7 , 8 ]. Our case is unique in that the patient developed pleural effusion with the longest recorded latency period of more than 70 years after silica exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicosis, which is a common occupational lung disease secondary to exposure to silica dust after an appropriate latency, only presents with PE infrequently [ 11 ]. Even so, in an autopsy series of 110 silicosis, pleural thickening was found in 64 (58%) cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, silicosis can produce right heart failure (9). Pleural effusions and extrapulmonary manifestations of silicosis are extremely rare presentations, but there are no significant data to suggest diffuse edema is present in this disease (10). Pleural biopsy findings were consistent with hyalinized collagen bundles with dust-filled histiocytes and interstitial fibrosis (11).…”
Section: Differential Diagnosismentioning
confidence: 99%